Strategi Dosen Dalam Manajemen E-Learning Guna Meningkatkan Hasil Belajar Mahasiswa di Perguruan Tinggi - Nisak Ruwah Ibnatur Khusnul; Aris Suharyadi (Universitas Kristen Satya Wacana, 2021)
The purpose of this research is to find out how lecturers' strategies in e-learning management to improve learning outcomes in college. In this study, strategi lecturer in e-learning management in question includes how to plan, implement, supervise, and evaluate in online learning (e-learning). This type of research uses a qualitative approach with descriptive methods. The subjects of the study are lecturers who do online learning and are able to improve the results of learning through e-learning. The research instrument uses interview guidelines and documentation. The data collection technique in this study is an interview with a strengthened on website e-learning display website documentation. Data analysis using data triangulation techniques. The results of this study showed that the lecturer's strategy in managing e-learning, including 1) Planning, namely drawing up a learning plan on the e-learning website, with a sub-view of RPS (lesson plan), learning achievements, diagnostic tests (pre-test), module materials, learning videos, journal links related to materials, discussion forums, tasks, and absorption tests (posttest). 3) Supervision is by utilizing the agreed e-learning time, monitoring process through zoom media, video conference and whatsapp group to know the activeness and atamodity of students in e-learning. 4) Evaluation, with diagnostic tests and absorption tests as an indicator of student atteanity in receiving e-learning materials and independent tasks to improve HOTS (higher order of thinking skills) students. Evaluation in maximizing e-learning content in the website is done with CIPP (context, input, process, and output) so that innovation from lecturers is always increasing.